2020
DOI: 10.1108/aeds-02-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Rural to urban migrant workers in China: challenges of risks and rights

Abstract: PurposeThe rapid urbanization of China brings in large number of migrant workers coming from rural areas. With the perspective of social integration, this study reviews the findings about economic livelihood, social integration and health related to migrant workers since China initiated economic reform. We show that (1) though the economic wellbeing of migrant workers has been improved significantly after they moved to cities, their economic standing is still lower than local residents; (2) though there is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In China, there were about 28.56 million migrant workers in 2020 [ 4 ], accounting for a considerable proportion of the total population. Compared with local residents, migrant workers are at a disadvantage in some aspects such as health insurance, labor security, social welfare, housing subsidies, and children’s education due to the administrative barriers of China’s household registration system (hukou) which plays an important role in social resource allocation [ 5 , 6 ]. Therefore, migrant workers have long been a vulnerable group of Chinese society.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there were about 28.56 million migrant workers in 2020 [ 4 ], accounting for a considerable proportion of the total population. Compared with local residents, migrant workers are at a disadvantage in some aspects such as health insurance, labor security, social welfare, housing subsidies, and children’s education due to the administrative barriers of China’s household registration system (hukou) which plays an important role in social resource allocation [ 5 , 6 ]. Therefore, migrant workers have long been a vulnerable group of Chinese society.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 90% of this industrial worker sample were migrants, who had been working migrants in Shenzhen for an average of 6 years. Research on similar populations reported commonly experiencing discrimination and exclusion from local residents, impeding the establishment and maintenance of social bonding [61,62]. Constant failures of social bonding could naturally serve as a source of defeat, and propagate anxious and depressive symptoms [15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, sentiment divergence is defined as the extent of different opinions or sentiments of users toward the same event from massive social media data (Cao et al, 2015). Due to lower education and professional skill, migrant workers are more likely to work in low-status occupations like construction, manufacturing and lowend service in urban areas (Yang and Qu, 2021). They cluster in industries with low wages, high labor intensity and poor employment environments, but benefit less from local economic growth and industrial mix than natives (Liu et al, 2021).…”
Section: Dual Images Of Migrant Workersmentioning
confidence: 99%